Waving the map for national identity: How cartography in Norway and Sweden was used as a nation-building tool in the eighteenth and nineteenth centuries - Lien, Anne Christine (ERDKUNDE, 2023)
Cartography has for centuries been used as a political instrument to support national pride, impact and influence, whether through use of a national prime meridian or local toponyms, the emphasising of the country’s extent through colour, or the underlining and even distorting of its position and size through projection. In Scandinavia, the eighteenth and nineteenth centuries were times of upheaval, during which regions changed political affiliation and nations formed shifting political unions. Norway had not been an independent nation since 1380, but by the turn of the nineteenth century, Norwegian national consciousness was emerging, in parallel with the rise of ideas about the national state in the rest of Europe. The purpose of this paper is to examine whether and how the rising focus on national identity in Norway was nurtured through cartography during the final decades of the union with Denmark (1380-1814) and the first decades of the new union with Sweden from 1814 (-1905). A further aim has been to consider how Sweden, as the senior union partner, might similarly have used cartography to keep the union together as a unity, in opposition to the Norwegian national self-assertion. A selection of Scandinavian maps from the late eighteenth century and throughout the nineteenth century have been analysed with a focus on cartographic elements with potential impact on national identity. The main results indicate that both Norwegian and Swedish maps of that time may have been used as instruments of political influence. The use of cartographic elements on the analysed maps in general seem to have strengthened Swedish hegemony on one side and Norwegian nationalism on the other side, thus reinforcing the political division of Scandinavia still seen today.